Pengaruh Visual Merchandising Terhadap Impulse Buying Melalui Positif Emotion Pada Usaha Fashion Di Kota Malang ( Studi Kasus Pada Usaha Distro & Cloting Inspired27 ) - Ayax Berrem Bernadi; Rois Arifin; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
abstractThis study aims to analyze the effect of visual merchandising on impulse buying through positive emotion in fashion businesses in the city of Malang. The population used is all Distro & Cloting Inspired27 customers. The sampling technique used purposive sampling method obtained a sample of 96 respondents. The data collection method in this study used the questionnaire method, the data analysis technique in this study used path analysis.Through this research, it can be concluded that visual merchandising (window display, mannequin display, floor merchandising and promotional signage) has a direct and significant effect on positive emotion, visual merchandising indirectly has a significant effect on impulse buying through positive emotion as an intervening variable on the customer of fashion distribution business. and clotting inspired 27. keywords : visual merchandising, positive emotion, impulse buying